2013
DOI: 10.1016/j.jadohealth.2012.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Homelessness Independently Predicts Injection Drug Use Initiation Among Street-Involved Youth in a Canadian Setting

Abstract: Purpose This longitudinal study examines the association between homelessness and injection drug use initiation among a cohort of street-involved youth in a setting of high prevalence crystal methamphetamine use. Methods Data were derived from the At-Risk Youth Study, a prospective cohort of street-involved youth aged 14 to 26 recruited between September 2005 and November 2011. Cox proportional hazards regression was used to identify factors independently associated with time to injection initiation. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
54
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 10 publications
9
54
1
2
Order By: Relevance
“…Previous studies suggest that crystal methamphetamine is a key risk factor for injection drug use among street-involved youth in our setting (15,23). However, our findings indicate that crystal methamphetamine may be uniquely risky for female youth.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Previous studies suggest that crystal methamphetamine is a key risk factor for injection drug use among street-involved youth in our setting (15,23). However, our findings indicate that crystal methamphetamine may be uniquely risky for female youth.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, to protect against reverse causation whereby reported behaviours were a consequence of drug injecting, all substance use variables were lagged to the previous available observation. In this way, we were able to assess behaviors that were reported prior to the injecting initiation event (15). Since participants could have varying durations between their last injecting naive and their first interview where they report injecting, the date of first injection was estimated as the midpoint between the first injecting naive follow up and the follow up visit where injecting was reported.…”
Section: Methodsmentioning
confidence: 99%
“…With respect to structural factors, the availability of housing and housing status (including homelessness) consistently appears as a risk factor for injection initiation across a range of settings [13,16,32]. For example, Roy et al found that homelessness was the key risk factor for injection initiation among street-involved youth in Montreal.…”
Section: Risk Factors For Injection Initiatesmentioning
confidence: 99%
“…42 Homelessness is an independent predictor of substance use. 43 Both homelessness and substance use are harmful yet common aspects of street life, 5,44,45 and both are associated with suicidality. 46,47 Qualitative research shows that homelessness, substance use, and adverse childhood experiences converge on feelings of hopelessness and of being "trapped," which contribute to suicide among street youth.…”
Section: Discussionmentioning
confidence: 99%